Decision-Making on Additional Power Supply for the Timor System: A Systematic Literature Review of Analytic Network Process Applications - Mahaprasetya, I Dewa Gde Budhita; Gunarta, I Ketut (Institut Riset dan Publikasi Indonesia, 2026)
This study employs a Systematic Literature Review (SLR) to synthesize empirical findings on the application of the Analytic Network Process (ANP) in energy planning and power-supply decision-making. The review identifies commonly used evaluation criteria, assessed alternatives, and strategic implications for electricity-system planning, particularly in constrained or semi-isolated systems such as the Timor System. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 framework, including identification, screening, eligibility assessment, and inclusion. Relevant literature was retrieved from Scopus and Google Scholar using keywords related to ANP, power-system planning, energy storage, generation expansion, and electricity decision-making. Of 52 records identified, eight studies satisfied the inclusion, eligibility, and quality-assessment criteria and were synthesized. The findings show that ANP effectively evaluates alternatives involving interdependent technical, operational, economic, environmental, and policy criteria. Battery Energy Storage Systems (BESS) and other flexible low-carbon technologies are generally preferred when reliability, flexibility, and policy alignment are prioritized, whereas conventional thermal generation remains competitive under cost-oriented scenarios. This review transforms dispersed ANP evidence into a structured decision-making framework for the Timor System and recommends evaluating future power-supply alternatives using reliability-oriented, scenario-based, and policy-aligned weighting instead of relying solely on economic comparisons.